The West Bank history , politics, society, and economy - Peretz, Don (Boulder, Colorado Westview Press, 1986)
This study of the West Bank was originally undertaken for the Middle East Institute in Washington, D.C., under the terms of its contract with the U.S. Defense Intelligence Agency. The study was compiled from a series of draft working papers. Covering The Late Ottoman period to 1967 and the second part looks at the West Bank under Israeli Occupation after 1967. (Google books)
​Part 1.The West Bank: The Late Ottoman period through 1967 1 The Ottoman era -- 2 The Mandatory era -- 3 The Jordanian era-- Part 2 The West Bank under Israeli Occupation, 1967 and After-- 4 The Israeli Dimension -- 5 Jewish settlement in the West Bank-- 6 The Military Government Administration -- 7 The Arab dmension -- 8 West Bank economy --  9 The West Bank and Middle East politics: Some future options 10 Conclusion.
Includes index. Bibliography p. 157-159
Keywords: History; PALESTINIANS; POLITICS; ECONOMIC CONDITIONS; HISTORY; WEST BANK; ISRAELI OCCUPATION OF PALESTINE 1948-; OTTOMAN PERIOD